THE ASSOCIATION BETWEEN ONLINE GAME ADDICTION AND DEPRESSION IN MEDICAL STUDENTS - Antonia Joscelin; Eva Suryani; Yunisa Astiarani; Satya Joewana (Universitas Negeri Gorontalo, 2021)
The rate of internet use is quite high among college students. Internet is used as a media to play online games, which if played extensively may lead to addiction. Excessive play of online games is found to be associated with decreased psychosocial wellbeing and may cause depressive mood. The rate of depression disorder in Indonesia, especially among college students is quite high. This research aims to find out the association between online game addiction and depression in preclinical students of Atma Jaya Catholic University of Indonesia's Medicine and Health Science Faculty.This research uses cross-sectional method on preclinical students of Atma Jaya Catholic University of Indonesia's Medicine and Health Science Faculty year 2017-2019. The instruments used are questionnaires (demographic, Game Addiction Scale, and Patient Health Questionnaire-9). Out of 215 respondents, 3,7% had online game addiction. It was found that the rate of mild depression is 34%, moderate depression is 18.1%, moderately severe depression is 7.4%, and severe depression is 2.3%. Statistical analysis indicates that there is a significant association between online game addiction and depression (p 0,05). In conclusion, there is an association between online game addiction and depression in preclinical students of Atma Jaya Catholic University of Indonesia's Medicine and Health Science Faculty.